Diversity and Community Structure of Fish in Saguling Hydroelectric Power Plant (PLTA) Area, Bandung Barat Regency - Muhammad Ainur Rafiq; Ulinuha Dzulfi Nuryanda; Hasbiyan Rosyadi; Muhammad Rahardian Adila Haqqi; Avandi Latrianto (3BIO: Journal of Biological Science, Technology and Management, 2026)
Aligning the sustainability effort of the Saguling Hydroelectric Power Plant (PLTA), Bandung Barat Regency, this study was conducted to understand the aquatic ecosystem balance through the diversity and community structure of the fish on those area. Data collection was conducted in July-September 2024 on 6 stations, which includes the environmental and fish diversity data through active method by direct capture and VES (Visual Encounter Survey), and also passive method through trapping and observation to the fish caught by fishermen or local residents. Data analysis was carried out through diversity, evenness, and species richness. Based on data collected, 570 fish from 22 species and 15 different families were found. The mostly found species were guppy (P. reticulata), pepetek (L. equulus), and red devil fish (a. labiatus). The environment of study area location in general has good circumstances of water quality to support fish lives and other fisheries activity (class 2 to 3) regarding to water quality standard. Based on ecological index calculation results, study area location has a medium diversity with a score of 2.548, high evenness with a score of 0.813, and medium species richness with a score od 3.464. While station 6 (Cicangkang Hilir) has the overall highest index compared to other stations.